Effectiveness of Accounting Information Systems, Leadership Style, Work Motivation and Employee Performance - Putu Febby Candra Lestari; I Gde Ary Wirajaya (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
Employee performance is the quality and quantity of work results achieved by employees in performing their work. This research was conducted to examine the effect of the influence of the effectiveness of accounting information systems, leadership styles and work motivation on employee performance. The study was conducted in Perumda Tirta Tohlangkir with a total of 52 respondents. The sample determination method uses non probability sampling with a saturated sampling technique. The data were collected by survey method with questionnaire technique and analyzed using multiple linear regression analysis techniques. The results showed that the effectiveness of accounting information systems had an effect but not significantly on employee performance. Leadership style positively affects employee performance. Work motivation has an effect but is not significant on employee performance.